Silver Nanoparticles (AgNPs) as Enhancers of Everolimus and Radiotherapy Sensitivity on Clear Cell Renal Cell Carcinoma - Mariana Morais; Vera Machado; Patrícia Figueiredo; Francisca Dias; Rogéria Craveiro; Joana Lencart; Carlos Palmeira; Kirsi S. Mikkonen; Ana Luísa Teixeira; Rui Medeiros (MDPI AG, 2023)
Nanomedicine's advent has promised to revolutionize different biomedical fields, including oncology. Silver Nanoparticles (AgNPs) showed promising results in different tumor models. Clear cell Renal Cell Carcinoma (ccRCC) is especially challenging due to its late diagnosis, poor prognosis and treatment resistance. Therefore, defining new therapeutic targets and regimens could improve patient management. This study intends to evaluate AgNPs' effect in ccRCC cells and explore their potential combinatory effect with Everolimus and Radiotherapy. AgNPs were synthesized, and their effect was evaluated regarding their entering pathway, cellular proliferation capacity, ROS production, mitochondrial membrane depolarization, cell cycle analysis and apoptosis assessment. AgNPs were combined with Everolimus or used to sensitize cells to radiotherapy. AgNPs are cytotoxic to 786-O cells, a ccRCC cell line, entering through endocytosis, increasing ROS, depolarizing mitochondrial membrane, and blocking the cell cycle, leading to a reduction of proliferation capacity and apoptosis. Combined with Everolimus, AgNPs reduce cell viability and inhibit proliferation capacity. Moreover, 786-O is intrinsically resistant to radiation, but after AgNPs' administration, radiation induces cytotoxicity through mitochondrial membrane depolarization and S phase blockage. These results demonstrate AgNPs' cytotoxic potential against ccRCC and seem promising regarding the combination with Everolimus and sensitization to radiotherapy, which can, in the future, benefit ccRCC patients' management.